1996
DOI: 10.1177/002199839603001201
|View full text |Cite
|
Sign up to set email alerts
|

Bearing Failure of Bolted Composite Joints. Part I: Experimental Characterization

Abstract: An investigation was performed to study the bearing failure of mechanically fastened fiber-reinforced laminated composite joints. Only double-lap metal/composite/metal bolted joints were investigated. The results of this study will be presented in two parts: experimental characterization and analytical prediction. This paper summarizes the experimental work. The major focus of the experiments was to characterize the bearing failure mechanism and mechanics, and to evaluate the effect of clamping pressure on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(78 citation statements)
references
References 13 publications
2
75
0
1
Order By: Relevance
“…8 that the bearing strengths in each group increase as the thickness scale increases. A similar result based on the thickness study has also been reported by Wang et al 23 The interpretation of the change in bearing strength due to the thickness scaling was more complicated than that due to in-plane scaling. In addition to the negative influence based on the Weibull theory for specimens subjected to pin loading (also true for specimens subjected to compressive loading reported in the section "Effect due to Compressive Strength"), there was apparently a positive contribution due to the thickness scaling.…”
Section: Size Effectssupporting
confidence: 86%
“…8 that the bearing strengths in each group increase as the thickness scale increases. A similar result based on the thickness study has also been reported by Wang et al 23 The interpretation of the change in bearing strength due to the thickness scaling was more complicated than that due to in-plane scaling. In addition to the negative influence based on the Weibull theory for specimens subjected to pin loading (also true for specimens subjected to compressive loading reported in the section "Effect due to Compressive Strength"), there was apparently a positive contribution due to the thickness scaling.…”
Section: Size Effectssupporting
confidence: 86%
“…From these failure modes only bearing damage produces a progressive failure, thus composite bolted joints are designed to fail under this mode. Bearing failure occurs in the material immediately adjacent to the contacting bolt surface due to primar ily compressive stresses and leading to a non linear behaviour of the composite plates [7].…”
Section: Introductionmentioning
confidence: 99%
“…The load arrangement has previously been used by Wang et al, (1996) to characterise bearing strengths of laminated FRPs for the aerospace industry. The Warwick University test arrangement is shown in Figure 5.…”
Section: A Test Methods For Pultruded Structural Shapesmentioning
confidence: 99%